Influence of Steel Fibers Content on Selected Mechanical Properties - Experimental Tests - Czajkowska, Agnieszka; Ingaldi, Manuela (Manufacturing Technology Journal, 2022)
The continuous development of construction due to the great needs of society and industry, the need to build newer and more durable buildings have meant that scientists all the time look for new opportunities to improve the quality of materials used in this field. Above all, concrete, as material commonly used in construction, has been the subject of research for many years in order to improve the properties. Already in antiquity there were the first attempts to modify the building material with fibers. Initially, they were organic fibers. However, the first patent dates from 1874, when A. Bernard patented the idea of strengthening concrete with steel filings [1]. Then, attempts were made to strengthen the concrete with long steel fibers, which was done by H. Alfsen in 1918. Further researches led N. Zitkiewic to test the strength and impact toughness of concrete with the use of pieces of mild steel wire [2]. Steel fibers in concrete were used for the first time by Romuladi and Baston in 1963. In the paper a comparative analysis of selected mechanical properties for concrete and fiber-reinforced concrete, e.g. compressive strength and Young's modulus, was presented. It was checked how the value of Young's modulus and the compressive strength of concrete change depending on the content of steel fibers. Three types of samples were tested: 1 - concrete, 2 - fiber-reinforced concrete containing 0.25% of steel fibers, 3 - fiber-reinforced concrete containing 0.50% of steel fibers. As the analysis has shown, the greater number of steel fibers is not directly proportional to the increase in its compressive strength or the value of Young's modulus.
Keywords: Concrete; Fiber-reinforced concrete; Compressive strength; Young's modulus